Core competencies, matching, and the structure of foreign direct investment: An update - Federico J. Díez; Alan C. Spearot (Federal Reserve Bank of Boston, 2013)
We develop a matching model of foreign direct investment to study how multinational firms choose between greenfield investment, acquisitions, and joint ownership. Firms must invest in a continuum of tasks to bring a product to market. Each firm possesses a core competency in the task space, but the firms are otherwise identical. For acquisitions and joint ownership, a multinational enterprise (MNE) must match with a local partner that may provide complementary expertise within the task space. However, under joint ownership, investment in tasks is shared by multiple owners and hence is subject to a holdup problem that varies with contract intensity. In equilibrium, ex ante identical multinationals enter the local matching market, and ex post, three different types of heterogeneous firms arise. Specifically, the worst matches are forgone and the MNEs invest greenfield; the middle matches operate under joint ownership; and the best matches integrate via full acquisition. We link the firm-level model to cross-country and industry predictions related to development and contract intensity, respectively, where greater contract intensity and a relatively more developed target market yield a higher share of full acquisitions. Using data on partial and full acquisitions across industries and countries, we find robust support for both predictions.
Keywords: F12; F23; 330; foreign direct; investment; multinational firms; joint venture; merger and acquisition; greenfield investment; incomplete contracts